2020
DOI: 10.1002/1348-9585.12115
|View full text |Cite
|
Sign up to set email alerts
|

Size of company of the longest-held job and mortality in older Japanese adults: A 6-year follow-up study from the Japan Gerontological Evaluation Study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This was one reason why we conducted separate analyses for each sex. A recent study showed that employees in a large company are in better health than those in a small one 38. As the target group of this study were employees of a large company, there is the possibility of such bias.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was one reason why we conducted separate analyses for each sex. A recent study showed that employees in a large company are in better health than those in a small one 38. As the target group of this study were employees of a large company, there is the possibility of such bias.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study showed that employees in a large company are in better health than those in a small one. 38 As the target group of this study were employees of a large company, there is the possibility of such bias. Heterogeneity of age gaps between age groups and limitation of the target ages may have weakened analyses, especially in younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of company size on psychological distress differed between those who worked from home and those that did not. The association between company size and psychological distress in previous studies was inconsistent (Inoue et al 2010;Kanamori et al 2020). This discrepancy may be attributable to the use of different indicators (company size vs. worksite size) or different survey years reflecting different economic situations.…”
Section: Discussionmentioning
confidence: 91%
“…This can be an important omission in our knowledge as 70% of workers in Japan work for small-sized and medium-sized enterprises, where people tend to work longer hours for less salary compared with those working for large companies 17 18. Some studies in Japan suggested that health outcomes tended to be worse among those working for small-sized and medium-sized companies than those working for larger companies 19 20. Third, limited studies have focused on gender differences in SC and health.…”
Section: Introductionmentioning
confidence: 99%